A novel, improved throughput bioassay for determining the delative speed of antimalarial drug action using fluorescent vitality probes - Laming, Dustin (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2020)
Malaria is one of the most prevalent diseases in Africa and Plasmodium falciparum is widely accepted as the most virulent of the malaria parasite species, with a fatality rate of 15 "“ 20 % of reported cases of infection. While various treatments have been accepted into early stage clinical trials, there has been little progress towards a proven vaccine. Pending a long-term solution, endemic countries rely heavily on the development of innovative drugs that are not only efficacious but are also quick acting. Traditional methods of evaluating antimalarial killing speeds via morphological assessments are inherently flawed by tedious, subjective interpretations of the heterogenous parasite morphology encountered in routine parasite culture conditions. This has led to the introduction of alternative assay formats to determine how rapidly compounds act on parasites in vitro: a parasite reduction ratio (PRR) assay that measures the recovery of parasite cultures from drug exposure; determining the shift in IC50 values of compounds when dose-response assays are carried out for different time periods; a bioluminescence relative rate of kill (BRRoK) assay that compares the extent to which compounds reduce firefly luciferase activity in transgenic parasites. Recent whole cell in vitro screening efforts have resulted in the generation of chemically diverse compound libraries such as the Medicines for Malaria Venture's Pathogen Box, which houses 125 novel compounds with in vitro antiplasmodial activity. Assessing the relative killing speeds of these compounds would aid prioritizing fast-acting compounds that can be exploited as starting points for further development. This study aimed to develop a bioassay using the calcein-acetoxymethyl and propidium iodide fluorescent vitality probes, which would allow the relative speed of drug action on Plasmodium falciparum malaria parasites to be assessed and ranked in relation to each other using a quantitative, improved throughput approach. Initially applied to human (HeLa) cells, the assay was used to compare the relative speeds of action of 3 potential anti-cancer compounds by fluorescence microscopy. Subsequently adapted to P. falciparum, the assay was able to rank the relative speeds of action of standard antimalarials by fluorescence microscopy and two flow cytometry formats. Application of a multiwell flow cytometer increased throughput and enabled the assessment of experimental compounds, which included a set of artemisinin analogs and 125 antimalarial compounds in the MMV Pathogen Box. The latter culminated in the identification of five rapidly parasiticidal compounds in relation to the other compounds in the library, which may act as benchmark references for future studies and form the basis of the next generation of fast acting antimalarials that could be used to combat modern, resistant malaria.
Keywords: Plasmodium falciparum; Malaria -- Treatment -- Africa; Antimalarials; Malaria vaccine